Returning mail-order goods: analyzing the relationship between the rate of returns and the associated costs - Björn Asdecker (Logistics Research, 2015)
Mail-ordering, particularly on the internet, has continually grown in importance over the last few years. This trend is expected to continue with no apparent end in sight. Liberal return policies have significantly contributed to this development by strengthening trust in both the individual retailers and the sales channel in general, but they do come at a price. This article is the first to systematically analyze the relation between the rate of returns and the associated costs. A circular model for the sales and returns process reveals a disproportionate relation between the two, which is further amplified once depreciation is considered. The model may serve decision-makers as an easy-to-use tool to systematically evaluate preventive returns management measures such as avoidance and gatekeeping.
Keywords: 650; Product returns; Mail-order business; Distance selling; Rate of returns; Product return costs